Os pais tão on: masculinidades, paternidades e performatividades de jovens pais na cidade de Manaus–AM - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The objective of this research is to expose the elements present in the performativities of the group of collaborating parents. The research included 16 parents, 14 cis and 2 trans, each of them with different depths of participation. The title “Parents are on” refers to the way in which exchanges with parents took place, especially in the first half of the research, most of the time, via the WhatsApp application, where we had a group. I arrived at the research tripod, elements highlighted in the parents' performativities, through these interactions. The elements that make up the tripod are affection and presence; providing and caring; silence and absences; some of these elements appear in the answers to the questions “what is it like to be a father?” and “what is an ideal/model father?” These elements are present in the parents' performativities and masculinities and are not necessarily expressed in the same words, for example, when we talk about fear or joy we are also talking about affection. I prioritized the speech of black and trans men, which converged with the availability of these parents during the research. However, I believe that even shorter participations were not only of great contribution, but also essential for the completion of the research. Activities with and without children are expressed throughout the text seeking to locate the elements of the tripod, and other threads that form the plot of this work, these are, for example, the relationship between performativities, masculinities, paternities, which need to be perceived in this same plot in which they are made up of other threads, such as the aforementioned elements, as well as the intersections between the parents of the research are also threads that constitute this plot. I used anonymity as a way to protect the identity of the parents, creating fictitious names, as well as subtracting details, since the members of the group themselves, for the most part, know each other, making this anonymity relative. Through the father's idea, the first elements emerge and shape the work. Parent’s relationships with their children, with their parents and with their friends are reported by the research parents themselves personally, in the WhatsApp group or individually.
Fathers online: masculinities, paternities and performativities of young fathers in Manaus–AM
Los Padres están online : masculinidades, paternidades y performatividades de padres jóvenes en la ciudad de Manaus – AM
Keywords: .; .; .; CIENCIAS HUMANAS: ANTROPOLOGIA: ANTROPOLOGIA URBANA; Performatividades; Masculinidades; Paternidades; Gênero; Interseccionalidade